The Influence of Emotional Intelligence and Coping Strategies on Employee Productivity Performance During COVID-19 Pandemic - Genty Lim Gen Tih; Abdul Hamid, Norhadilah (Research in Management of Technology and Business, 2021)
At a period when corona diseases are spreading all over the globe, the output in the US and Europe has declined dramatically by 7.2 percent and 8.2 percent respectively. This is because employees are feeling anxious about the spread of corona viruses. The goal of this research is to identify the level of emotional intelligence and coping strategies on employee productivity performance, to examine the relationship between emotional intelligence and coping strategies toward employee productivity performance and to determine the significant difference on employee productivity performance between local and foreign workers. This research was conducted at a manufacturing company, The Phoenix Press Sdn Bhd, located in Penang, Malaysia.. A quantitative research method involving online survey was used in this research. The population consisted of the production line employees and manager. Hence, random sampling was employed. All the data were analyzed through SPSS using different analysis which are descriptive, correlational and t-test analysis. The findings in this research show that emotional intelligence and coping strategies have positive effect on employee productivity performance. Lastly, the most important contribution of this study is it allows industries to take an earlier step to focus more on emotional intelligence and coping strategies in order to improve worker job performance.